Beckman Microzone Model R-110 Densitometer, Duostat power supply, and electrophoresis cell (1960)
Beckman introduced a Microzone Electrophoresis System in 1964 and the Model R-110 Microzone Densitometer in 1967. Densitometers measure density by scanning electrophoresis media.
Keywords: Electrophoresis; Densitometry; Scientific apparatus and instruments; Electrophoresis--Equipment and supplies; Power resources; Beckman Instruments, Inc.